Efecto de la cal, nitrógeno y manganeso en el rendimiento y la concentración de nutrimentos en el maíz - Villachica L., H.; Cabrejos H., Óscar (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Three important problems were studied in an Inceptisol from the humid subtropical zone of Peru, with a pH 4.9 and very low CEC. These problems were soil acidity, N deficiency and high Mn concentration. Furthermore, the task to face was to know wich of the following situations has more influence on the Mn availability: the acidic reaction of the N-fertilizer or the Mn application to the soil. In order to study these problems under green house conditions, the soil was limited to pH 5.3, 5.7, 5.9 6.1, and five levels of N and Mn were applied. The statistical design used was the central composite rotatable factorial. Dry matter yields and nutrient concentration of the top part of corn (Zea mays L.) were measured. The determination coefficients for the dry matter yield and for the foliar concentrations of N, Ca, Mg, Mn, Fe and Cu were very high. This results indicated that the regressions were predicted and represented accurately by their respective equations. The yield was increased by low N dosages; however, high dosages of N or Mn showed negative effect on corn plant growth. A positive effect of N-fertilizer in the Mn absorption and a negative effect of this latter in dry matter production was observed. The increase in Mn absorption was greater with the N dosages than with the applications of the micronutrient to the soil itself. This experiment shows once more that in order to have a good yield response liming applications had to be in accordance with the exchangeable acidity. Nevertheless, a depression effect of lime on Mn absorption and a decrease in the negative effect on yield was found to be relevant. The foliar concentrations of Ca, Mg, Zn and Fe were enhanced by the application of ammonium nitrate to the soil, while the lime application decreased Zn abssorption. The foliar nutrient levels were not influenced by the Mn applications, except when this was applied with N.